2021
DOI: 10.3390/ejihpe11030068
|View full text |Cite
|
Sign up to set email alerts
|

Is Electronic Health Literacy Associated with Learning Outcomes among Medical Students in the First Clinical Year?: A Cross-Sectional Study

Abstract: Medical students tend to use the internet as a primary resource when seeking health information. This study aims to assess the patterns of internet use, eHL level, and learning outcomes with eHL among medical students at Chiang Mai University. A cross-sectional study was conducted among 88 medical students in the first clinical year. The eHL level was determined using the Thai version of the electronic Health Literacy Scale or eHEALS. The patient case report scores were obtained representing the learning outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…This study showed a significant relationship between nutrition literacy and students’ exposure to nutrition-related information in universities and places of study. This finding is consistent with previous studies [ 52 , 53 ] and suggests that individuals who receive nutrition information in universities and have completed relevant nutrition courses have better nutrition literacy [ 52 ]. Additionally, using food and nutrition information obtained through various media channels may be challenging for university students due to the university’s unique environment [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study showed a significant relationship between nutrition literacy and students’ exposure to nutrition-related information in universities and places of study. This finding is consistent with previous studies [ 52 , 53 ] and suggests that individuals who receive nutrition information in universities and have completed relevant nutrition courses have better nutrition literacy [ 52 ]. Additionally, using food and nutrition information obtained through various media channels may be challenging for university students due to the university’s unique environment [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Of course, It is also associated with the number of nutrition courses and nutrition education contents. As NL is literacy focusing on nutrition-related information, medical students with more exposure to medical and health information in faculty courses perform better compared to other non-medical courses (36). However, with the exception of students pursuing medicine-related majors, university students are unlikely to have access to nutrition education (21).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated [ 3 ] that the formative change proposed by online education had positive effects on academic performance, compared to the traditional face-to-face method. This has been particularly beneficial for younger students [ 3 , 7 ]. As has been observed, it has also given rise to [ 1 ] the justification for not using the masks, despite the recommendations, and the moral disconnection caused by dark personality traits, the so-called dark triad, as a self-regulatory mechanism to exclude moral self-censorship and justify ignoring recommendations to use the mask [ 1 ].…”
mentioning
confidence: 99%
“…As has been observed, it has also given rise to [ 1 ] the justification for not using the masks, despite the recommendations, and the moral disconnection caused by dark personality traits, the so-called dark triad, as a self-regulatory mechanism to exclude moral self-censorship and justify ignoring recommendations to use the mask [ 1 ]. Despite the fact that current medical students are digital natives, there is still a need to improve their competencies in information and communication technology, enhance their skills and reinforce confidence to use eHealth information [ 7 ]. It is necessary for this reason to introduce literacy concepts into medical pedagogy along with workshops to improve evidence-based search and evaluation techniques to in order to acquire future competencies to foster health literacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation